SYNDROME OF POST-ISCHEMIC PERFUSION DISORDERS AFTER DELIVERY - I. V. Shlyk; I. V. Bovkun; D. V. Sokolov; E. G. Gavrilova; S. G. Meschaninova (Вестник анестезиологии и реаниматологии)
The article describes the clinical case of reperfusional syndrome after caesarean section in the new mother with giant liver tumor which manifested through development of multi-organ dysfunction with hemodynamic disorders, acute respiratory distress syndrome, and acute liver lesion. This clinical case confirms the hypothesis that reperfusion syndrome can complicate the course of pregnancy and post-delivery period and shows that the issue of intra-abdominal hypertension in the pregnant requires further investigation.